2010
DOI: 10.1186/cc9326
|View full text |Cite
|
Sign up to set email alerts
|

Nitroglycerin can facilitate weaning of difficult-to-wean chronic obstructive pulmonary disease patients: a prospective interventional non-randomized study

Abstract: IntroductionBoth experimental and clinical data give convincing evidence to acute cardiac dysfunction as the origin or a cofactor of weaning failure in patients with chronic obstructive pulmonary disease. Therefore, treatment targeting the cardiovascular system might help the heart to tolerate more effectively the critical period of weaning. This study aims to assess the hemodynamic, respiratory and clinical effects of nitroglycerin infusion in difficult-to-wean patients with severe chronic obstructive pulmona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
11

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 32 publications
1
27
0
11
Order By: Relevance
“…Notably, it was recently reported that patients with diastolic dysfunction may present impaired diastolic reserve under stressful conditions [27], and this possibly explains weaning intolerance. In line with the above, other authors suggested that weaning outcomes may improve with the application of strategies aiming to manage heart failure (i.e., diuretics, nitroglycerin) [17,28,29]. In our cohort, we found that patients who failed weaning presented known precipitating factors for LV diastolic dysfunction (i.e., age, arterial hypertension, increased wall thickness and LV mass, and COPD) [30].…”
Section: Discussionsupporting
confidence: 64%
“…Notably, it was recently reported that patients with diastolic dysfunction may present impaired diastolic reserve under stressful conditions [27], and this possibly explains weaning intolerance. In line with the above, other authors suggested that weaning outcomes may improve with the application of strategies aiming to manage heart failure (i.e., diuretics, nitroglycerin) [17,28,29]. In our cohort, we found that patients who failed weaning presented known precipitating factors for LV diastolic dysfunction (i.e., age, arterial hypertension, increased wall thickness and LV mass, and COPD) [30].…”
Section: Discussionsupporting
confidence: 64%
“…Such increases may not be tolerated by patients with compromised heart function, which becomes the cause or a cofactor of weaning failure, 26 described as "weaning-induced cardiovascular compromise." 26,27 One limitation of our study was that we did not acquire more comprehensive information to decide whether subjects could be transferred out of the ICU or not. Additionally, we only followed the subjects for 28 d in the ICU, and we did not collect subject data on the 14th or 21st day of mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…In a nonrandomized study of difficult-to-wean COPD patients, the authors showed that nitroglycerin is well tolerated and may facilitate weaning due to its stabilizing effect on hemodynamics in these patients. 102 Other aspect to take into account is the method to carry out the spontaneous breathing trial. In this way, Cabello et al 103 compared three methods of performing weaning trials in 14 patients (7 of whom had COPD) who had previously failed a T-piece trial.…”
Section: Mechanical Ventilationmentioning
confidence: 99%